The combined effect of Moxifloxacin and Ciprofloxacin against multidrug-resistant Klebsiella pneumoniae - Hossain, Mehrin; Chakrabortty, Deepita (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.